THE COACH’S ROLE IN THE DEVELOPMENT OF YOUNG ATHLETES: INTEGRATING PERFORMANCE, EDUCATION, AND HUMAN VALUES - Mello, Luis Eduardo (Revista Sistemática, 2022)
The development of young athletes extends beyond technical skill acquisition and competitive success, encompassing psychological growth, social integration, and character formation. Within this context, the coach plays a pivotal role as mentor, educator, and role model, exerting substantial influence on both athletic performance and personal development. This article examines the importance of the coach in the holistic development of young athletes, drawing upon personal experience and established academic literature in sport pedagogy and youth development. By integrating experiential knowledge from high-performance sport with evidence-based coaching principles, the discussion highlights how coaching practices can foster resilience, motivation, ethical behavior, and lifelong engagement in sport. The analysis underscores the responsibility of coaches to create supportive environments that prioritize long-term development and well-being alongside athletic achievement.